Chrononutrition behaviors during pregnancy: maternal nighttime eating increases the risk of preterm birth - Rodríguez-Cano, Ameyalli M.; Medel-Canchola, Berenice; González-Ludlow, Isabel; Pizano-Zarate, Maria Luisa; Estrada-Gutierrez, Guadalupe; Perichart-Perera, Otilia (Frontiers in Nutrition, 2025)
IntroductionMaternal nutrition in pregnancy influences birth outcomes and offspring health; chrononutrition behaviors could be potentially linked to perinatal complications such as preterm birth (PTB).AimTo evaluate if gestational chrononutrition behaviors influence PTB risk.MethodsHealthy pregnant women (n = 215) from the ongoing OBESO cohort (Mexico City) were studied. Diet (24 h-recall) and sleep-schedule were evaluated in each trimester, obtaining average fasting duration (hours, last–first meal), minutes from waking-up to breakfast (AM-latency), and from dinner to sleeping (PM-latency). Nighttime eating (9:00 pm–5:59 am on three recalls) was registered. Short sleep was defined as <6 h/night. The presence of gestational complications (PE, preeclampsia; GDM, gestational diabetes; GH, gestational hypertension), gestational weight gain (GWG), multivitamin (MV) consumption (low: 0–1 trimesters, moderate: 2 trimesters, high: 3 trimesters) was recorded. Gestational age at resolution was computed and PTB was classified (<37 weeks, first-trimester ultrasound). Logistic regression models were performed to evaluate the association between each chrononutrition behavior and the presence of PTB.ResultsMean fasting was 11.8 ± 1.2 h; AM, PM latency were 104.4 ± 76.7, 112.3 ± 54.5 min, respectively. Nighttime eating was present in 33% (n = 71) of women. Gestational complications prevalence was 16.3% (n = 35). Half of women had a high MV-consumption (55.8%, n = 120). PTB was present in 8.8% (n = 19) of pregnancies. A higher frequency of PTB was observed with nighttime eating (15.5% vs. 5.6%; p = 0.16), with low MV-consumption (low: 25%, moderate: 5.6%, high: 7.5%; p = 0.011) and with short sleep (63.2% vs. 29.1%; p = 0.002). Regression models showed that nighttime eating (OR:5.716, 95%CI:1.724–18.951), low MV-consumption (OR:7.937, 95%CI:1.873–33.639), short sleep (OR:4.551, 95%CI:1.392–14.879) and PE (OR:9.016, 95%CI:1.772–45.881) were positively associated with PTB risk. Other maternal variables in the model (R2 = 0.318, p = 0.010) were not associated (age, obesity, parity, GDM, GWG, energy intake).ConclusionMaternal nighttime eating during pregnancy is associated with a higher risk of PTB.